2020
DOI: 10.1080/17843286.2020.1822078
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: contribution of clinical characteristics and laboratory features for early detection of patients with high risk of severe evolution

Abstract: Background: The aim of this study was to identify early clinical and laboratory predictive factors of a severe coronavirus disease 2019 (COVID-19). Methods: A retrospective study was conducted on adult patients hospitalized for COVID-19 in our hospital. Diagnosis was based on a positive real-time reverse transcription-polymerase chain reaction (RT-PCR) on nasopharyngeal samples. The cohort was divided into two groups, i. e. a favorable evolution (FE) group and an unfavorable evolution (UFE) group, including in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Our study demonstrated that patients who had multiple comorbidities were seen to have a higher severity of COVID-19. Thus, more varieties of comorbidities were also associated with increased severity in the AIRD group of patients, similar to the general population [16,17].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our study demonstrated that patients who had multiple comorbidities were seen to have a higher severity of COVID-19. Thus, more varieties of comorbidities were also associated with increased severity in the AIRD group of patients, similar to the general population [16,17].…”
Section: Discussionmentioning
confidence: 55%
“…The median time from symptoms onset to admission was 25 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Laboratory results showed that 60% of the patients with SLE, 33.3% with RA and the only one Rhupus patient developed lymphopenia, while 28.6% (6/21) had lymphopenia at entry. The median level of lymphocyte counts at entry was 1.41×10 9 /L.…”
Section: Baseline Characteristics and Laboratory Findingsmentioning
confidence: 99%
“…Wang et al 's study 10 showed that male, elder age, diabetes cardiovascular diseases, chills, dyspnea, SO 2 value of ≤93%, WBC counts of >10×10 9 /L and large consolidated opacity on CT images were all risk factors for aggravation of illness. Edith Sepulchre et al 11 found that older age, male gender, comorbidities and dyspnea at admission constituted significantly worse prognosis factors. Feng He et al 12 found that older age, Wuhan exposure history, diarrhea, chronic kidney disease, elevated myoglobin, elevated white blood cell and C-reactive protein were independent risk factors for severe patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the majority of individuals with COVID-19 exhibiting only mild symptoms or even being asymptomatic, there are patients who develop serious complications, underlining the fact that it is crucial to identify who is at higher risk of a worse prognosis and to recognize reliable outcome predictors in a timely manner for improving patient management. As a result, the personalized medicine approach appears to be highly appropriate for the study of COVID-19, considering the wide spectrum of severity and variable phenotypes [ 147 ], including asymptomatic, mildly symptomatic, severe symptomatic requiring hospitalization, and respiratory failure due to acute respiratory distress syndrome (ARDS) [ 148 ]. Omics-scale studies on SARS-CoV-2 are quickly emerging and have a huge potential to resolve the infection pathophysiology [ 149 ], highlighting biologic pathways, modifiable risk factors, and critical information to allow early interventions [ 150 , 151 ].…”
Section: Development and Perspectives For Italian Public Health Gementioning
confidence: 99%